A rare case of BRAF V600E‐mutated epithelioid glioblastoma with a sarcomatous component. Issue 3 (5th January 2020) - Ishikawa, Ryou; Kadota, Kyuichi; Hayashi, Toshitetsu; Kimura, Nachino; Inoue, Kousuke; Ibuki, Emi; Kagawa, Seiko; Kushida, Yoshio; Okada, Masaki; Miyake, Keisuke; Tamiya, Takashi; Nobusawa, Sumihito; et al.
Abstract : Epithelioid glioblastoma is a rare subtype of glioblastoma, but the coexistence of a sarcomatous component is even rarer. An 80‐year‐old woman was admitted to our hospital with somnolence. Magnetic resonance imaging revealed a cystic lesion with a solid component in the left temporal–parietal lobe. Histopathological examination of the resected tumor revealed three components; namely, typical glioblastoma, sarcomatous and epithelioid components at a ratio of about 5:3:2. All components were immunohistochemically positive for vimentin and mutated BRAF (V600E) and showed focal expression of glial fibrillary acidic protein and cytokeratin AE1/AE3, but they were negative for isocitrate dehydrogenase 1. Genetic analysis revealed that both the sarcomatous and epithelioid components harbored BRAF T1799A (V600E) mutation and homozygous deletion of cyclin‐dependent kinase inhibitor 2A/B. We diagnosed this tumor as epithelial glioblastoma with a sarcomatous component. Our results indicate that even when the epithelial component is not dominant, immunohistochemical and genetic investigation of BRAF mutations is useful for the diagnosis of glioblastoma subtypes. In particular, although the prognosis of epithelial glioblastoma is poor, potentially effective targeted therapies for BRAF V600E‐mutated tumors are available.